Reviews - big data: the important dimensions - UiTM, Faculty of Business and Management (UiTM, 2019)
Big Data is a term used to describe the abundance of data sets, in various forms and types; structured, semi structured or unstructured, that comes from various sources; known and unknown, that are too large and complex to be dealt with (Miloslavskaya, & Tolstoy, 2016). The term big data analytics refers to the collection of data and transforming them into information that are usable and meaningful, commonly for decision making (Babanli, 2017) The history of big data goes way back before the age of computers and digitalisation where data were tirelessly collected, stored and processed manually (Miloslavskaya, & Tolstoy, 2016). During these times, analysis and results took years and required large amounts of man hours, since data processing was a painstaking, time consuming and expensive process. Nonetheless, big data processing has evolved over the years due to its significance in providing meaningful information to assist effective decision making. With the development of information system (IS), however, major shortcoming with big data has been resolved (Gandomi & Haider, 2015). Analysts are now able to collect, process and analyse data much faster and with ease.